Development and characterization of antibody reagents to assess anti-PEG IgG antibodies in clinical samples. (August 2015) - Krishna, Murli; Palme, Holly; Duo, Jia; Lin, Zheng; Corbett, Martin; Dodge, Robert; Piccoli, Steven; Myler, Heather; Pillutla, Renuka; Desilva, Binodh
Background: Polyethylene glycol (PEG) is a polymer that can be conjugated with therapeutic proteins. Monitoring anti-PEG antibodies in human subjects may be required as part of immunogenicity assessment. The lack of well-characterized anti-PEG reagents have limited our understanding of anti-PEG humoral response.Results: Antibodies reactive to PEG were engineered with a human IgG1 Fc. Surface plasmon resonance and plate-based methods demonstrated that their binding was dependent on molecular weight (MW) of PEG. Specificity experiments using chemical analogs identified their specificity.Conclusion: Affinity, specificity and MW of PEG are critical characteristics that impact interactions of anti-PEG antibodies with PEG. These attributes especially MW of PEG and the assay formats may impact the ability to detect anti-PEG antibodies.